Investigation of an outbreak of malaria in a non- endemic coastal area, Kerala, Southern India - Raveendran, Sandhya; P. S., Rakesh; Dev, Soumya; Prasannakumar, Prathibha; Vijayakumar, Nithin (International Journal Of Community Medicine And Public Health, 2016)
Background: Kollam district, Kerala state, Southern India was free of indigenous transmission of malaria for years. Three cases of malaria were reported to the district surveillance unit of integrated disease surveillance project from coastal areas within town limits of Kollam district on 19th September 2015. Methods: An outbreak investigation was initiated which included stimulated reporting from all hospitals, mass and contact survey, entomological assessment and exploratory interview with cases. Results: A total of six cases of malaria were identified from a total population of 3785. All cases were males. All cases were P. falciparum and P. vivax (mixed) type malaria. Anopheles stephensi breeding sites were found in abandoned boats, near the temporary huts at the seashore, where all the cases used to sleep during night. Median duration of date of symptom onset to the date of diagnosis as malaria was nine days (range 5-18 days). Half of the patients had at least three visits to a health care facility before a diagnosis of malaria was made. Conclusions: There was a delay in diagnosing malaria and hence continuous and ongoing sensitization may be needed to keep the index of suspicion high among clinicians. Success in preventing malaria resurgence in Kerala requires a paradigm shift from a focus on reactive temporary short term response to a proactive long term planned and comprehensive strategy.